2021
DOI: 10.1186/s12870-021-02876-z
|View full text |Cite
|
Sign up to set email alerts
|

Lasting consequences of psyllid (Bactericera cockerelli L.) infestation on tomato defense, gene expression, and growth

Abstract: Background The tomato psyllid, Bactericera cockerelli Šulc (Hemiptera: Triozidae), is a pest of solanaceous crops such as tomato (Solanum lycopersicum L.) in the U.S. and vectors the disease-causing pathogen ‘Candidatus Liberibacter solanacearum’. Currently, the only effective strategies for controlling the diseases associated with this pathogen involve regular pesticide applications to manage psyllid population density. However, such practices are unsustainable and will eventually lead to wide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 63 publications
(31 reference statements)
1
5
0
Order By: Relevance
“…This hypothesis is supported by the tomato plant geotropism experiments which showed that Lso-infected plants are likely unresponsive to auxin signaling, which is an outcome predicted by the transcriptomic results which suggested auxin-responsive genes are suppressed in Lso-infected tomatoes. The results of the current research parallel the transcriptomic analysis characterizing the genes differentially expressed in response to psyllid infestation [ 19 , 22 ], which also demonstrated long-term consequences for plant expression following biotic challenge. Interestingly, some of the significant differences between uninfected and infected plants were the general promotion of jasmonic acid-related pathways and cell wall modification (Supplementary Tables 5 and 6 ), and these same processes were affected even more in LsoB-infected plants (Supplementary Tables 12 and 13 ).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This hypothesis is supported by the tomato plant geotropism experiments which showed that Lso-infected plants are likely unresponsive to auxin signaling, which is an outcome predicted by the transcriptomic results which suggested auxin-responsive genes are suppressed in Lso-infected tomatoes. The results of the current research parallel the transcriptomic analysis characterizing the genes differentially expressed in response to psyllid infestation [ 19 , 22 ], which also demonstrated long-term consequences for plant expression following biotic challenge. Interestingly, some of the significant differences between uninfected and infected plants were the general promotion of jasmonic acid-related pathways and cell wall modification (Supplementary Tables 5 and 6 ), and these same processes were affected even more in LsoB-infected plants (Supplementary Tables 12 and 13 ).…”
Section: Discussionsupporting
confidence: 57%
“…The MDS distance plot also demonstrated weak separations between control and Lso-free psyllid-infested plants as well as a separation between LsoA- and LsoB-infected plants. These results suggested that overall gene expression was most different between uninfected and infected plants but also suggested that psyllid infestation and Lso haplotype have significant consequences for tomato plant gene expression [ 22 ]. This interpretation is supported by the binomial distribution of differential expression (DE) values among all sample libraries (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In tomatoes, SlCM2 has been also shown to be upregulated under drought stress ( Filiz et al, 2019 ). Among downregulated genes, Solyc08g008630.3.1 (Log 2 Fc = −3.34; tomato chloroplastic beta-carotene isomerase D27 Dwarf27 ) is involved in strigolactone and beta-carotene biosynthesis and has been found to be downregulated in psyllid-infested tomato plants ( Harrison et al, 2021 ). Solyc04g050930.3.1 (Log 2 Fc = −2.07; tomato violaxanthin de-epoxidase VDE ) is involved in the carotenoid biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to SCN data set, In RAD, the novel associations among DE-lncRNAs and the major nematode-responsive DEGs were elegantly recognized. NTF2 as overexpressed regulators in infected resistant soybean roots (de Sá et al, 2012), RING/ FYVE/PHD zinc finger superfamily protein as positive regulator of downstream targets under nematode infection to establish resistance at transcriptional level (Song et al, 2019), GSH introduced in the modulation of giant cell metabolism and manipulation of ROS pathway (Baldacci-Cresp et al, 2012;Wu, 2019), glycosyl hydrolases family with a cell wall-modifying role (Nyaku et al, 2013), Aquaporin-like superfamily gene as a membrane transport protein-coding gene and nematodeinduced gene (Hammes et al, 2005), signal peptide peptidase-like2 as a defense response inducer (Harrison et al, 2021), and CAP superfamily gene as highly induced protective gene (Hamamouch et al, 2011) were some nematode responseassociated DEGs identified modules of RAD which showed interaction with DE-lncRNAs.…”
Section: Discussionmentioning
confidence: 99%